2021
DOI: 10.1016/j.ipm.2020.102434
|View full text |Cite
|
Sign up to set email alerts
|

User and item-aware estimation of review helpfulness

Abstract: In online review sites, the analysis of user feedback for assessing its helpfulness for decision-making is usually carried out by locally studying the properties of individual reviews. However, global properties should be considered as well to precisely evaluate the quality of user feedback. In this paper we investigate the role of deviations in the properties of reviews as helpfulness determinants with the intuition that "out of the core" feedback helps item evaluation. We propose a novel helpfulness estimati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Second, H2, H3, and H4 are supported significantly, which means that informative signals positively influence users’ decision-making process. These results are consistent with extant studies [ 46 , 49 , 76 ]. Informative signals include review readability, depth, and spelling.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Second, H2, H3, and H4 are supported significantly, which means that informative signals positively influence users’ decision-making process. These results are consistent with extant studies [ 46 , 49 , 76 ]. Informative signals include review readability, depth, and spelling.…”
Section: Discussionsupporting
confidence: 94%
“…Third, H5 is significantly supported, that is to say, patients’ negative sentiments about physician’s service quality have significant effects on perceived IH. The positive relation between user sentiments and IH has been tested before [ 48 , 76 ]. The results of the present study showed that negative emotions in reviews showed a positive effect on review helpfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Our future work includes the development of the envisaged algorithms and their evaluation, offline and with real users. Moreover, we plan to enhance the extraction of aspects from reviews by using review helpfulness analysis [13,15,24,35] to select valuable consumer feedback and filter out low-quality reviews.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed model was successfully validated, and critical components that would make an opinion relevant to readers were discovered. The study findings have added to related literature by offering more comprehension of the structural characteristics (quantitative and qualitative) of reviews and their effect on RH [ 18 , 19 , 31 ]. The findings indicate that both the review- and service-related signals significantly and positively influence perceived RH.…”
Section: Introductionmentioning
confidence: 93%
“…Fang et al [ 17 ] indicated that text readability significantly influences perceived RH. Mauro et al [ 18 ] revealed that review wordiness is a meaningful predictor of RH. The study of Malik and Hussain [ 19 ] indicated that discrete emotions are the most dominant emotions with greater influence on perceived RH.…”
Section: Introductionmentioning
confidence: 99%